3(w+2)-w=2(w+1)=5

Simple and best practice solution for 3(w+2)-w=2(w+1)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w+2)-w=2(w+1)=5 equation:



3(w+2)-w=2(w+1)=5
We move all terms to the left:
3(w+2)-w-(2(w+1))=0
We add all the numbers together, and all the variables
-1w+3(w+2)-(2(w+1))=0
We multiply parentheses
-1w+3w-(2(w+1))+6=0
We calculate terms in parentheses: -(2(w+1)), so:
2(w+1)
We multiply parentheses
2w+2
Back to the equation:
-(2w+2)
We add all the numbers together, and all the variables
2w-(2w+2)+6=0
We get rid of parentheses
2w-2w-2+6=0
We add all the numbers together, and all the variables
4!=0
There is no solution for this equation

See similar equations:

| -37-7x=6(-x-7) | | x/8+2.5=-10.5 | | -1/2d=-3 | | 4730=3s+5(s+150) | | (10x+1)(x)=82 | | -7/8x=-42 | | 2c−2=2 | | 2x–10=-4x+14 | | 7h=4-2h | | 15=2n=3n | | x+6.9=9.25 | | 3x+4/7=9.5 | | 105-x-2x=120+2x | | 3g-1=g | | 5/8(4(x)-16)=20 | | X-1+8x=36 | | 6+{w-10}=5 | | 2+10n+12-1=9n+14n | | -2(x)+3-x=3(x)-15 | | (10x+1)+x=82 | | 6n+4=8(-n+4) | | 4(3x-1)=17+5x | | -5=3x-32/4 | | (10x+1)x=82 | | 3(a)+17=32 | | -1-k=-5 | | -6m+3m=-6 | | 9c=8+5c | | 10n=45.50 | | 3x/5-2=-11 | | 2^((2x+1))-9(2^x)+4=0 | | 0.074n=74 |

Equations solver categories